Proceso de atención nutricional en paciente femenino de 66 años de edad con diagnostico hipertensión arterial. - Pacheco Zapata, Yarely Salome (2024)
The present case report shows a 66-year-old female patient with hypertension and overweight. A nutritional assessment identified multiple factors contributing to her condition, including a high body mass index (BMI) and an excessive intake of sodium, calories and fat, and a nutritional plan was designed to reduce sodium intake and increase potassium intake in order to implement good lifestyle changes. A follow-up was established to evaluate the effectiveness of the nutritional plan and adjust it if necessary. The final recommendations included the reduction of sodium intake and the incorporation of foods rich in potassium, the adaptation to a balanced diet, portion control of meals and adequate hydration, in addition to physical activity that will help prevent complications or risks in her arterial hypertension, thus achieving an adequate and healthy lifestyle for the patient.